Multiplikasi Tunas Andalas (Morus macroura Miq. var. macroura) dengan Menggunakan Thidiazuron dan Sumber Eksplan Berbeda secara In Vitro - Eron Swandra; M Idris; Netty W Surya (Jurnal Biologi Universitas Andalas, 2012)
The aim of this research was to study the responses of Andalas somaclone explant and to determine the best concentration of thidiazuron (TDZ) for shoot multiplication. It used completely randomized design (CRD) in factorial with two experimental factors and three replications. The first factor was source of nodal explant; explant without colchicine treatment and explant with colchicine treatment (0,1% for 72 hours immersion time). The second factor was five levels of TDZ which were 0; 0.125; 0.250; 0.375 and 0.500 mg/l. The results showed that all treatment gave life percentage of explant 100%. The best timing of shoot formation were 5.33 day after cultured (dac) from explant without colchicine treatment and 5 dac from explant with colchicine treatment. TDZ 0,500 mg/l from explant without colchicine treatment showed the highest number of shoots (12.67) while TDZ 0.375 mg/l for explant with cholchine treatment (10.67). The highest length of shoot were showed in TDZ 0.125 mg/L from explant without colchicine treatment (32.33 mm) and explant with colchicine treatment (38.33 mm). The length of shoot decreased along increasing of TDZ concentration, while the number of shoot increased along increasing of TDZ concentration.Keywords: Morus macroura Miq. var. macroura, multiplication, thidiazuron, explant, in vitro